4.2 Wartości liczbowe wyrażen algebraicznych
1. Oblicz wartości poniższych wyrażeń dla x=-1, y = 4 i 2 = 3.
3x + z
x+2
32 - 2y + x
3.-1)+3=0
2z-y
2y + 6x
xyz + 10
5x + 2y+
yz + 10x
Y-Z + x
5.(-1) + 5 = 6
2x2 +
(2-x): 2
12 - 5z - x
12-59


Odpowiedź :

Odpowiedź:

x = -1, y = 4, z = 3

3x + z = 3×(-1) + 3 = -3+3 = 0

x+z = -1+3 = 2

3z - 2y + x = 3×3 -2×4 -1 = 9-8-1 = 0

3×(-1)+3= -3+3 = 0

2z-y = 2×3 - 4 = 6-4 = 2

2y + 6x = 2×4 + 6×(-1) = 8-6 = 2

xyz + 10 = (-1)×4×3 = -12+10 = -2

5x + 2y = 5×(-1) + 2×4 = -5+8 = 3

yz + 10x = 4×3 + 10×(-1) = 12-10 = 2

Y-Z + x = 4-3-1 = 0

(-1) + 5 = 4

2x2 = 2×(-1) × 2 = -2×2 = -4

(2-x): 2 = (2+1)÷2 = 3÷2 = 1,5

12 - 5z - x = 12-5×3+1 = 12-15+1 = -2

12-59 = -47